Mature teratoma in a neonate presenting as an intraoral cystic lesion: A case report - Singh, Srijan (Indian Journal of Child Health, 2020)
Teratomas are germ cell neoplasms that can occur in the cervical and craniofacial regions. A male neonate, antenatally diagnosed with intraoral cystic lesion, presented with a large 5 cm × 5 cm cystic swelling at birth arising from the palate. Alpha-fetoprotein levels of the patient were >1000 IU/L and beta-human chorionic gonadotropin levels were